A especificidade do trabalho docente no PROEJA : um estudo sobre a experiência do Instituto Federal de Educação, Ciência e Tecnologia Sul-Rio-Grandense Campus Sapucaia do Sul/RS - Heckler, Gisele Lopes (Universidade do Vale do Rio dos Sinos, 2012)
This investigation is situated among the fields of Young and Adult Education and Professional Education integrated to Brazilian High Schools. It aims at helping develop concepts specifically related to teaching at a Program called PROEJA, a National Program for the Integration of Professional Education and Basic Learning for Young and Adults which deals with both Young and Adult Education and Professional Education. This study took place at the Instituto Federal de Educação, Ciência e Tecnologia Sul-Rio-Grandense, in the Sapucaia do Sul/RS campus. The methodology adopted is a qualitative one, in a methodological bricolage that joined data collection following the documentary method of interpretation and the work of Marie-Christine Josso under the perspective of formation-research. Besides the specific laws and the PROEJA framework document, the literary review approaches the subjects of teaching, formation and teaching for young and adults (EJA), as well as the formation of teachers for Professional Education. Based on collective interviews done with groups of discussion, it was possible to conclude that the teachers of PROEJA are conscious about the specificities of the EJA students, and that they want to attend them. Another conclusion is that the specialization course about PROEJA at IFSUL in the Sapucaia do Sul/RS campus had minimum attendance. There are no other instruction courses with this aim at the moment to fulfill the necessities of the teachers -- specially substitute ones, who are temporarily employed. The causes of resistance or adherence to the program are related to the educational experiences that teachers previously had, as well as to their political and pedagogical positions.
Keywords: Trabalho docente; Educação profissional; Educação de jovens e adultos; PROEJA; Teaching; Professional education; Young and adult education; ACCNPQ::Ciências Humanas::Educação